The role of madrasah principals in implementing the independent curriculum: A case at a State Islamic Senior High School in Central Java - Sukmawati, Rusdiyani; Farid, Imam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study explores the role of madrasah principals in implementing the independent curriculum at Madrasah Aliyah Negeri Batang. Employing a qualitative method with a case study approach, this research selected participants using purposive sampling. Data were collected through interviews, observations, and document analysis. The data analysis employed Miles, Huberman, and Saldana's interactive model, encompassing data condensation, data display, and conclusion drawing. The findings indicate that the role of madrasah principals in implementing the independent curriculum encompasses three main aspects: planning, execution, and monitoring. In the planning phase, the principals engage in program design and participate in professional development training to enhance curriculum implementation. During execution, their roles include forming a curriculum development team, preparing the madrasah operational curriculum (Kurikulum Operasional Madrasah, KOM), and establishing a project coordinator team to strengthen the profile of Pelajar Pancasila, known locally as Profil Pelajar Pancasila. In the monitoring phase, principals conduct administrative and classroom learning supervision to ensure effective curriculum implementation. These findings underscore the pivotal leadership roles of madrasah principals in supporting curriculum innovation.